2020
DOI: 10.1108/ijqrm-10-2019-0312
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Total Quality Management for sustainability in Indian organizations

Abstract: PurposeThe paper aims to identify key human and operational focused barriers to the implementation of Total Quality Management (TQM). It develops a comprehensive structural relationship between various barriers to successfully implement TQM for sustainability in Indian organizations.Design/methodology/approachWith the help of expert opinions and extant literature review, we identified the case of TQM failure companies and barriers to implement TQM effectively. Interpretive Structural Modeling (ISM) and fuzzy M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…Likewise, one of the Baldrige Foundation's criteria for performance excellence is the role of leaders in creating an organizational focus on action, including transformational change in an organization's structure and culture. The importance of leadership in TQM implementation is also demonstrated by the fact that the primary causes of TQM failure are attributable to management weaknesses or having an unsupportive leadership role (Dilawo and Salimi, 2019; Krajcsák, 2019; Kumar et al , 2020). The success of TQM implementation is dependent, to a great extent, on the appropriate leadership style.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, one of the Baldrige Foundation's criteria for performance excellence is the role of leaders in creating an organizational focus on action, including transformational change in an organization's structure and culture. The importance of leadership in TQM implementation is also demonstrated by the fact that the primary causes of TQM failure are attributable to management weaknesses or having an unsupportive leadership role (Dilawo and Salimi, 2019; Krajcsák, 2019; Kumar et al , 2020). The success of TQM implementation is dependent, to a great extent, on the appropriate leadership style.…”
Section: Introductionmentioning
confidence: 99%
“…The competition has increased at all levels of customer satisfaction viz. cost, quality, speed and variety (Kumar et al, 2020). Even the functional products which relied on cost-optimized delivery at times have to compete on speed and extra quality aspects.…”
Section: Customer Relationshipmentioning
confidence: 99%
“…Many research and studies are published every year related to the factors responsible for the success or not success of TQM implementation (Sreedharan and Sunder, 2018;Talapatra and Uddin, 2019). Kumar et al (2020b) and Bou and Beltran (2005) found the reasons that organizations give little awareness to human resource practices and develop quality culture from the manufacturing companies.…”
Section: Introductionmentioning
confidence: 99%